Targeted transferosomal delivery of cetirizine: A new approach to alopecia management - Noha Talal Zelai (PLoS ONE, 2026)
Introduction Androgenetic alopecia is common in males and females; its prevalence increases with age. It affects the social life of individuals worldwide. The main problem associated with conventional minoxidil treatment is the risk of facial hypertrichosis. Cetirizine (CET), an antihistamine, may induce hair growth by increasing prostaglandin E2 expression. Therefore, Objectives: This study aimed to incorporate several CET formulations into transferosomes (TFS) and determine their optimal physicochemical properties. The optimal formulation was evaluated for its growth-promoting potential in vivo. Methods The effect of CET-TFS was assessed by observing hair growth and quantifying insulin-like growth factor-1 (IGF-1) and vascular endothelial growth factor (VEGF) mRNA and protein levels in mice. Results CET-TFS significantly enhanced hair growth in mice and stimulated high IGF-1 and VEGF mRNA and protein levels. Conclusion These findings suggest that CET-TFS is a promising alternative to traditional hair growth medications. Additional toxicity and histopathological studies are required to confirm its suitability.